2003
DOI: 10.2174/1381612033391784
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and its Role During Pregnancy: From Ovulation to Delivery

Abstract: Nitric oxide (NO) is a major paracrine mediator and important regulatory agent in various female reproductive processes, such as ovulation, implantation, pregnancy maintenance, labor and delivery. Ovulation: Circulating NO-products are increased during follicle development and decreased right after ovulation. INOS-inhibition results in a 50% reduction of ovulation, an effect completely reversed by an NO. Endometrium/Implantation: NO also regulates endometrial functions such as endometrial receptivity, implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 0 publications
3
94
0
4
Order By: Relevance
“…Furthermore, arginine stimulates the AKT1-mTOR/FRAP1-RPS6K-RPS6 cell signaling pathways to increase proliferation and migration of porcine (Kong et al, 2012) and ovine (Kim et al, 2011) trophectoderm cells during peri-implantation period. The positive impact of L-arginine supplementation during the peri-implantation period of pregnancy is due in part to the production of NO, since this is crucial for embryonic development and implantation (Maul et al, 2003;Wang X.Q. et al, 2014a).…”
Section: L-argininementioning
confidence: 99%
“…Furthermore, arginine stimulates the AKT1-mTOR/FRAP1-RPS6K-RPS6 cell signaling pathways to increase proliferation and migration of porcine (Kong et al, 2012) and ovine (Kim et al, 2011) trophectoderm cells during peri-implantation period. The positive impact of L-arginine supplementation during the peri-implantation period of pregnancy is due in part to the production of NO, since this is crucial for embryonic development and implantation (Maul et al, 2003;Wang X.Q. et al, 2014a).…”
Section: L-argininementioning
confidence: 99%
“…The importance of NO as a regulator of early developmental events has been established by studies that demonstrated that the oocyte and preimplantation embryo are exposed to NO, and oocyte maturation, preimplantation embryogenesis and implantation require NO (Biswas et al, 1998;Gagioti et al, 2000;Maul et al, 2003;Novaro et al, 1997;Purcell et al, 1999;Sengoku et al, 2001;Shukovski and Tsafriri, 1995;Telfer et al, 1995). Moreover, in vitro and in vivo studies showed that administration of either NOS inhibitors or NO donors hinders development of preimplantation embryos (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical ripening is an active process resembling an inflammatory reaction, which involves a complex cascade of degradative enzymes accompanied by degradation and disorganization of collagen framework, increased water content, and rearrangement of extracellular matrix proteins and glycoproteins [14,15]. Among factors regulating cervical ripening (i.e, mechanical factors, estrogens, cytokines, neuro-peptides, and other inflammatory agents), prostaglandins are regarded to have a crucial role [16].…”
Section: Discussionmentioning
confidence: 99%